Farmer’s knowledge, attitude and practices on safety, quality and post harvest management of brinjal and tomato in some selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2020)
Abstract Not AvailableBangladesh J. Agril. Res. 44(4): 695-702, December 2019